Update on Intensive Neuromonitoring for Patients with Traumatic Brain Injury: A Review of the Literature and the Current Situation - KOIZUMI, Hiroyasu (Neurol Med Chir (Tokyo), 2014)
Intracranial pressure (ICP) measurements are fundamental in the present protocols for intensive care of patients during the acute stage of severe traumatic brain injury. However, the latest report of a large scale randomized clinical trial indicated no association of ICP monitoring with any significant improvement in neurological outcome in severely head injured patients. Aggressive treatment of patients with therapeutic hypothermia during the acute stage of traumatic brain injury also failed to show any significant beneficial effects on clinical outcome. This lack of significant results in clinical trials has limited the therapeutic strategies available for treatment of severe traumatic brain injury. However, combined application of different types of neuromonitoring, including ICP measurement, may have potential benefits for understanding the pathophysiology of damaged brains. The combination of monitoring techniques is expected to increase the precision of the data and aid in prevention of secondary brain damage, as well as assist in determining appropriate time periods for therapeutic interventions. In this study, we have characterized the techniques used to monitor patients during the acute severe traumatic brain injury stage, in order to establish the beneficial effects on outcome observed in clinical studies conducted in the past and to follow up any valuable clues that point to additional strategies for aggressive management of these patients.